N-Benzoimidazole/Oxadiazole Hybrid Universal Electron Acceptors for Highly Efficient Exciplex-Type Thermally Activated Delayed Fluorescence OLEDs - Yuan, Wenbo; Yang, Hannan; Zhang, Mucan; Hu, Die; Sun, Ning; Tao, Youtian (Frontiers in Chemistry, 2019)
Recently, donor/acceptor type exciplex have attracted considerable interests due to the low driving voltages and small singlet-triplet bandgaps for efficient reverse intersystem crossing to achieve 100% excitons for high efficiency thermally activated delayed fluorescence (TADF) OLEDs. Herein, two N-linked benzoimidazole/oxadiazole hybrid electron acceptors were designed and synthesized through simple catalyst-free C-N coupling reaction. 24iPBIOXD and iTPBIOXD exhibited deep-blue emission with peak at 421 and 459 nm in solution, 397 and 419 nm at film state, respectively. The HOMO/LUMO energy levels were -6.14/-2.80 for 24iPBIOXD and -6.17/-2.95 eV for iTPBIOXD. Both compounds could form exciplex with conventional electron donors such as TAPC, TCTA and mCP. It is found that the electroluminescent performance for exciplex-type OLEDs as well as the delayed lifetime was dependent with the driving force of both HOMO and LUMO energy offsets on exciplex formation. The delayed lifetime from 579-2045 ns was achieved at driving forces close to or larger than 1 eV. Two TAPC based devices possessing large HOMO/LUMO offsets of 1.09-1.34 eV exhibited the best EL performance, with maximum external quantum efficiency (EQE) of 9.3% for 24iPBIOXD and 7.0% for iTPBIOXD acceptor. The TCTA containing exciplex demonstrated moderate energy offsets (0.88-1.03 eV) and EL efficiency (~4%), while mCP systems showed the poorest EL performance (EQE < 1%) and shortest delayed lifetime of < 100 ns due to inadequate driving force of 0.47-0.75 eV for efficient exciplex formation.